PENGARUH INVESTMENT OPPORTUNITY, FINANCING COMPANY, PROFITABILITY, CASH AND MARKET TO BOOK VALUE TERHADAP DIVIDEND PAYMENT POLICY PADA PERUSAHAAN MAKANAN DAN MINUMAN - STEVEN YAP (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
This study was conducted to examine the effect of the investment opportunity set, financing company, profitability, cash, and market to book value to dividend payment policy in companies listed Stock Exchange Securities Indonesia. The purpose of this study was to analyze the effect of the investment opportunity, financing company, profitability, cash, and market to book value to dividend payment policy in companies listed on the Stock Exchange of Securities Indonesia in 2008-2014. The population of about 15 food and beverage companies list in Indonesia Stock Exchange period 2008-2014. This research used purposive sampling. The results show that investment opportunity and profitability have an effect on dividend payment policy. While the financial company, cash, and market to book value does not affect the dividend payment policy.